1992
DOI: 10.2134/jpa1992.0383
|View full text |Cite
|
Sign up to set email alerts
|

Control of Pathogenic Mycorrhizal Fungi in Maintenance of Soil Productivity by Crop Rotation

Abstract: Pathogenic mycorrhizal fungi may be a major reason crops must be rotated to maintain soil productivity. We studied the role such fungi may have in the maintenance of productivity of soil for tobacco (Nicotiana tabacum L.) by rotation with tall fescue (Festuca amndinacea Schreb). Tall fescue ‘Kentucky 31’ and continuous tobacco plots were established on a central Kentucky field previously shown to be infested with the mycorrhizal fungus Glomus macrocarpum Tul and Tul., the cause of a stunt disease of tobacco. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…An extreme example of a mycorrhizal fungal association that decreases plant performance is observed in an intensively managed agricultural system in Kentucky, USA . A series of field and glasshouse studies has shown that colonization of tobacco by an endemic isolate of Glomus macrocarpum significantly reduces root length, aboveground biomass, and fiowering (Modjo & Hendrix 1986;Jones & Hendrix, 1987;Modjo, Hendrix & Nesmith, 1987;Hendrix, Jones & Nesmith, 1992). Although this isolate of G. macrocarpum is strongly parasitic (pathogenic) on tobacco in field soils with extremely high P, it does not appear to have parasitic effects on other crops.…”
Section: (3) Genotypic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extreme example of a mycorrhizal fungal association that decreases plant performance is observed in an intensively managed agricultural system in Kentucky, USA . A series of field and glasshouse studies has shown that colonization of tobacco by an endemic isolate of Glomus macrocarpum significantly reduces root length, aboveground biomass, and fiowering (Modjo & Hendrix 1986;Jones & Hendrix, 1987;Modjo, Hendrix & Nesmith, 1987;Hendrix, Jones & Nesmith, 1992). Although this isolate of G. macrocarpum is strongly parasitic (pathogenic) on tobacco in field soils with extremely high P, it does not appear to have parasitic effects on other crops.…”
Section: (3) Genotypic Factorsmentioning
confidence: 99%
“…Although this isolate of G. macrocarpum is strongly parasitic (pathogenic) on tobacco in field soils with extremely high P, it does not appear to have parasitic effects on other crops. Furthermore, it appears to have some specificity for tobacco because, in field studies, G. macrocarpum populations (and stunt-disease) can be controlled by rotation with Festuca (containing an endophyte that inhibits G. macrocarpum) as effectively as by fumigation (Hendrix et al, 1992;An, Guo & Hendrix, 1993;Hendrix, Guo & An, 1995).…”
Section: (3) Genotypic Factorsmentioning
confidence: 99%
“…Mycorrhizal associations have been considered to be parasitic in cases where the costs outweigh the benefits, as occurs in several cropping systems (Hendrix, Jones & Nesmith, 1992;Johnson et al, 1997). However, crops that benefit from mycorrhizas may eventually replace those that do not, because of crop rotation or the implementation of sustainable agricultural systems.…”
Section: Synchronised Developmentmentioning
confidence: 99%
“…Fredeen and Terry (1988) observed stunting of soybean roots and shoots by Glomus fasciculatum. In barley (Black and Tinker 1979) and tobacco (Hendrix et al 1992), a negative relationship between colonization and yield has been observed. Other instances of plant stunting by mycorrhizal fungi have been observed (Tinker 1978;Modjo and Hendrix 1986).…”
Section: Mycorrhizal Fungi In Relation To Crop Developmentmentioning
confidence: 99%